Pedagogy and the practice of science : historical and contemporary perspectives - Kaiser, David (Inside technology., 2005)
"Pedagogy and the Practice of Science provides the first sustained examination of how scientists and engineers training shapes their research and careers. The wide-ranging essays move pedagogy to the center of science, studies, asking where questions of scientists' training should fit into our studies of the history, sociology, and anthropology of science. Chapter authors examine the deep interrelations among training, learning, and research and consider how the form of scientific training affects the content of science. They investigate types of training - in cultural and political settings as varied as Victorian Britain, interwar Japan, Stalinist Russia, and Cold War America - and the resulting scientific practices